Digital light processing of complex-shaped 3D-zircon (ZrSiO4) ceramic components from a photocurable polysiloxane/ZrO2 slurry. Issue 23 (1st December 2021) - He, Chong; Cao, Yueqi; Ma, Cong; Liu, Xinger; Hou, Feng; Yan, Liwen; Guo, Anran; Liu, Jiachen
Abstract: Explorations in the stereolithography fabricated polymer-derived ceramics are still far from maturity. Herein, a novel preceramic slurry, which consists of a photocurable epoxy-acrylic siloxane and particle-size gradated ZrO2 fillers, was digital light processing shaped into 3D preceramic precursors. By taking advantage of the high reactivity of in-situ formed silica from the polysiloxane, 3D-zircon product can be synthesized through the sintering reaction between the polysiloxane and ZrO2 particles in the precursor at a low temperature. During the sintering process, ZrSiO4 phase starts to appear at the temperature of 1200 °C. A proper particle-size distribution of the ZrO2 filler, 20 wt% of micropartciles and 4 wt% of nanoparticles, not only endowed the ceramic slurry with a low viscosity but also increase the purity of the zircon products. Besides, the addition of sintering aid NaF can promote the sintering reaction between the polysiloxane and ZrO2 particles while increase the crystalize degree of the 3D-zircon products.